Impact of SARS-CoV-2 infection on neurodegenerative and neuropsychiatric diseases: A delayed pandemic? - P.J. Serrano-Castro; G. Estivill-Torrús; P. Cabezudo-García; J.A. Reyes-Bueno; N. Ciano Petersen; M.J. Aguilar-Castillo; J. Suárez-Pérez; M.D. Jiménez-Hernández; M.Á. Moya-Molina; B. Oliver-Martos; C. Arrabal-Gómez; F. Rodríguez de Fonseca (Neurología (English Edition), 2020)
Introduction: SARS-CoV-2 was first detected in December 2019 in the Chinese city of Wuhan and has since spread across the world. At present, the virus has infected over 1.7 million people and caused over 100 000 deaths worldwide. Research is currently focused on understanding the acute infection and developing effective treatment strategies. In view of the magnitude of the epidemic, we conducted a speculative review of possible medium- and long-term neurological consequences of SARS-CoV-2 infection, with particular emphasis on neurodegenerative and neuropsychiatric diseases of neuroinflammatory origin, based on the available evidence on neurological symptoms of acute SARS-CoV-2 infection. Development: We systematically reviewed the available evidence about the pathogenic mechanisms of SARS-CoV-2 infection, the immediate and lasting effects of the cytokine storm on the central nervous system, and the consequences of neuroinflammation for the central nervous system. Conclusions: SARS-CoV-2 is a neuroinvasive virus capable of triggering a cytokine storm, with persistent effects in specific populations. Although our hypothesis is highly speculative, the impact of SARS-CoV-2 infection on the onset and progression of neurodegenerative and neuropsychiatric diseases of neuroinflammatory origin should be regarded as the potential cause of a delayed pandemic that may have a major public health impact in the medium to long term. Cognitive and neuropsychological function should be closely monitored in COVID-19 survivors. Resumen: Introducción: La infección por el coronavirus SARS-CoV-2 originada en diciembre de 2019 en la región china de Wuhan ha adquirido proporciones pandémicas. A día de hoy ha ocasionado más de 1,7 millones de contagios y más de 100.000 muertes en todo el mundo. La investigación científica actual se centra en el mejor conocimiento de la infección aguda y de sus estrategias terapéuticas. Dada la magnitud de la epidemia, planteamos una revisión especulativa sobre las posibles consecuencias en patología neurológica a medio/largo plazo, con especial atención a enfermedades neurodegenerativas y neuropsiquiátricas con base neuroinflamatoria, teniendo en cuenta la evidencia directa de afectación neurológica a causa de la infección aguda. Desarrollo: Revisamos de forma sistemática lo conocido sobre los mecanismos patogénicos de la infección por SARS-CoV-2, la repercusión de la tormenta de citoquinas sobre el sistema nervioso central y su persistencia en el tiempo y las consecuencias que la neuroinflamación puede tener sobre el sistema nervioso central. Conclusiones: El SARS-CoV-2 es un virus neuroinvasivo capaz de provocar una tormenta de citoquinas que podría convertirse en persistente en población seleccionada. Aunque nuestra hipótesis tiene alto componente especulativo, la repercusión que esta situación puede tener en la puesta en marcha y progresión de enfermedades neurodegenerativas y neuropsiquiátricas con base neuroinflamatoria debe ser considerada como posible germen de una pandemia demorada que podría tener un gran impacto en salud pública a medio o largo plazo. Se hace necesario un estrecho seguimiento de la salud cognitiva y neuropsiquiátrica de los pacientes supervivientes a infección COVID-19.